Analisis Faktor-Faktor Yang Mempengaruhi Prokrastinasi Skripsi Pada Mahasiswa: Studi Kepustakaan - Jalal, Novita Maulidya (CV. Kalimasada Group, 2024)
The aim of this research is to analyze the factors that influence thesis procastrination. This research method uses library research. This research used 6 scientific articles related to factors that influence students' attitudes towards procrastination in working on their thesis. The results of this research show that students' behavior of procrastinating on their thesis is caused by internal and external factors in students. Internal factors are students' interests and attitudes in working on their thesis, as well as students' knowledge in working on their thesis. External factors include home conditions and support from supervisors. However, gender has no effect on the delay in the thesis. The implications of this research are useful for students, families and supervisors to support students' completion of their theses.